THE INFLUENCE OF COMPANY SIZE AND COMPANY GROWTH ON STUDY CAPITAL STRUCTURE IN MULTINATIONAL COMPANIES IN THE CONSUMPTION GOODS INDUSTRY - Adisty Azia Riska; Rico Nur Ilham; Nurlela; Wahyuddin (Universitas Efarina, 2023)
Capital structure is a balance between long-term debt and own capital, where capital structure is part of the financial structure. The existence of factors that influence capital structure is important as a basis for determining the composition of a company's optimal capital structure. The aim of this research is to determine or analyze the influence of company size and company growth on the capital structure of multinational consumer goods companies recorded on the IDX for the 2018-2022 period. The population in this study was 19 companies with 95 observations. Data analysis used in this research uses a method consisting of classical assumption tests, hypothesis tests and partial tests. The research results show that partially the company size variable has a positive and insignificant effect on capital structure. Meanwhile, the company growth variable has a negative and insignificant effect on capital structure.